Formulation Characterization of Statistically Optimized Naproxen Nanocrystals with Quality by Design - Sindhuri, Polepalli (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: The present objective of the study is to prepare nanoparticles of naproxen and then converting them into a suitable dosage form. Initially, the nanosuspension of naproxen is prepared using anti-solvent precipitation technique. The ideal and best formation obtained with the application of DOE. The best nanosuspension is freeze dried to get nanoparticles which is used for further study. In addition, the various process parameters which have a potential influence on the formulation are also studied. Methods: Solventanti- solvent precipitation method was employed as the preparation technique. A full factorial design (24) is used to design the experiment. Based on the previous studies and literature review, the parameters were selected. The experimental design is designed in such a way to assess various parameters such as critical process parameters, material attributes, and process parameters. Naproxen nanosuspensions were lyophilized with mannitol. The experimental data obtained were subjected to statistical analysis using various methods such as regression and ANOVA. Other evaluation procedures were followed to determine the various characteristics of the formulation and dissolution and pharmacokinetic studies are also performed. Results: The DOE and factorial design showed the point prediction as stirring time of 22.5 min and rate of injection as 0.4 ml/min, solvent-antisolvent ratio of 1:15, and stabilizer drug concentration of 1:7.5. The nanoparticles were found to be intact in SEM/TEM analysis and there were no drug interactions between the formulation ingredients. The zeta potential was found to be 50.2 mv. The pharmacokinetic analysis of nanoparticles showed AUC of 836 ng/ml which is twice obtained with that of pure drug. Other parameters like bioavailability of the formed nanoparticles have improved significantly when compared with that of pure naproxen. Conclusion: Naproxen nanosuspensions have been successfully prepared and the various process parameters which have an effect on the characteristics are studied. The predicted formulation has been prepared and evaluated for various parameters and found pharmacokinetically better when compared to pure drug.